Serum Pentraxin 3 Concentration in Neonatal Sepsis - Battal, Fatih; Bulut, Özgül Emel; Yıldırım, Şule; Aylanç, Hakan; Kaymaz, Nazan; Uysal, Sema (Journal of Pediatric Infectious Diseases, 2019)
Objective Neonatal sepsis is one of the most important causes of neonatal morbidity and mortality. Symptoms and signs of neonatal sepsis can be silent; therefore, laboratory investigation is necessary in cases of doubt or if there are risk factors. Early diagnosis is important for early intervention and treatment. The most valuable method for diagnosis is blood culture; however, false positivity due to contamination or false negativity despite ongoing fatal bacterial infections can be seen. Pentraxin 3 is a prototype of the long pentraxin family. It has some differences from C-reactive protein (CRP) in terms of gene organization and localization and production site. It is effective in the early phase of inflammation and it is detected as an early marker of sepsis in adults. The aim of this study was to investigate whether pentraxin 3 can be used as a marker in neonatal sepsis.Materials and Methods Thirty newborns with suspected sepsis with antenatal history or the presence of clinical signs of sepsis, such as hypo/hyperthermia, feed intolerance, lethargy, hypotonia, irregular cardiac rhythms, bradycardia, cyanosis, apnea, respiratory distress, or metabolic acidosis, were enrolled in the study as a case group, and 28 healthy newborns were included as a control group. Serum pentraxin 3, procalcitonin, CRP, and hemogram in the study group and serum procalcitonin and pentraxin in the control group were examined.Results Serum pentraxin 3 (pg/mL) and serum procalcitonin (ng/mL) levels were 2,273.82 ± 1,260.75 and 0.86 ± 0.52 in the case group and 957.41 ± 268.00 and 0.19 ± 0.18 in the control group (p < 0.001 for both), respectively.Conclusion The present study showed that serum pentraxin 3 levels may be a useful marker in the diagnosis of neonatal sepsis.
Keywords: neonatal sepsis; CRP; procalcitonin; pentraxin 3